Study on Insulin Like Growth Factor-1 As a Marker of Severity of Liver Dysfunction in Patients with Liver Cirrhosis - Raha, Aloke Kumar; Hoque, Mohammad Izazul; Mahtab, Mamun Al; Ahmad, Nooruddin; Rahman, Salimar; Khan, Mobin (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2019)
Background: Insulin Like Growth Factor-1 (IGF-1) is a polypeptide hormone predominantly synthesized in liver. It has been reported that serum IGF-1 concentrations low in hypopitutuitarism, malnutrition and various diseases particularly in patients with chronic liver disease. The aim of the study was to see the level of IGF-1 in patients with cirrhosis and its relation with severity of liver dysfunction. Materials and Methods : This study was carried out in the Department of Hepatology, Bangabandhu Sheikh Mujib Medical University (BSMMU) Dhaka, Bangladesh. 40 persons (30 patients of cirrhosis of liver and 10 healthy individuals) were selected and grouped as Group-1 : 10 Child grade A patient, Group - 2 : 10 Child grade B patient, Group - 3 : 10 Child grade C cirrhotic patients and Group - 4 : 10 healthy subjects. Patients with recent antiviral therapy, acute illness, hepatocellular carcinoma and spontaneous bacterial peritonitis were excluded from the study. IGF-1 was measured using IMMULITE, DPC, USA which employs automated chemiluminescent immunoassays. Results : Among 30 cirrhotic patients 26 were male and 4 were female. Mean age was 38.83 ± 14.08 years. Etiology of cirrhosis was hepatitis B virus in 23 patient, hepatitis C virus in 1 patient, Cryptogenic in 6 patients. Healthy subjects were hepatitis B and C virus negative with normal liver function test and mean age was 36.40 ± 7.76 years, Mean serum IGF-1 was 82 ± 10.85 ng/ml in Child grade A, 50.77 ± 7.47 ng/ml in Child grade B, 29.69 ± 3.17 ng/ml in Child grade C patients and 130.96 ± 2.43 ng/ml in healthy individuals. Conclusion : Serum level of IGF -1 is low in patients with cirrhosis of liver than healthy individuals and reflects the severity of liver dysfunction in different clinical stage. Chatt Maa Shi Hosp Med Coll J; Vol.18 (1); Jan 2019; Page 3-7